Prevalence of human papillomavirus infection in Argentinean women attending two different hospitals prior to the implementation of the National Vaccination Program - Chouhy, Diego (2013)
Cervarix vaccine was included in the National Immunization Program of Argentina in 2011 but data about the local distribution of human papillomavirus (HPV) infection in women exposed to the virus are scarce. This cross-sectional study determined the prevalence and type distribution of HPV infection in unvaccinated women attending routine gynecological screening in two public hospitals located in Buenos Aires and Santa Fe, Argentina. Socio-demographic, sexual behavior, and co-factors information was obtained from all participants (Buenos Aires, n=429; Santa Fe, n=433). Cervicovaginal swabs were tested with an MY11/09 primer-based assay and with the CUT primer system targeting mucosal/cutaneous HPVs. Participants from Buenos Aires showed significantly higher rates of HPV infection (52.4% vs. 40.6%), of multiple infections (24.2% vs. 16.4%), and of low-risk (20.3% vs. 13.9%) and high-risk types (44.1% vs. 33.3%) than those from Santa Fe. HPV-66 (Buenos Aires: 17%) and HPV-16 (Santa Fe: 8.5%) were the most prevalent types. Novel HPV-66 putative subtype and variants were identified. Vaccine types 16 and 18 were frequent (Buenos Aires: 13.5%; Santa Fe: 10.2%) but few participants had co-infections with both (Buenos Aires: 1.4%; Santa Fe: 0.2%). A common risk factor for HPV infection was having a new sexual partner in the last year (Buenos Aires: OR 2.53, P<0.001; Santa Fe: OR 1.85, P=0.04). This study provides valuable baseline data for future assessment of the impact of massive vaccination in Argentina and it underlines the use of additional HPV testing strategies, such as the CUT system, for surveillance and vaccinology.